¿Un liberal al frente de la Iglesia católica en México? Antonio J. Paredes: tres apologías - González Morfín, Juan (Jahrbuch für Geschichte Lateinamerikas, 2019)
Between 1914 and 1919 many of the episcopal sees of Mexico were abandoned by their respective bishops and were in the hands of different vicars. Antonio J. Paredes, vicar-general for the archdiocese of Mexico, in a pragmatic way knew how to guide the Catholic Church in the midst of turbulent circumstances, although for his pragmatism and his closeness to the revolutionaries, at various times he seemed to betray the principles of the Church that he represented. The Catholic prelates in exile frequently expressed before the Holy See their misgivings about Paredes. However, for almost five years he was sustained in his position and, in the end, the results of his management at the head of the Catholic institution reveal that his performance was highly satisfactory. The study of this figure allows us to approach an unexplored page of the State-Church relations in Mexico: that of ecclesiastical cooperation with the revolutionary regime during the Paredes period; though that performance has been frequently attacked. The purpose of this article is to study these attacks and present some apologies that allow for a more balanced judgment on this general-vicar of the metropolitan archdiocese.